The Effect of Apparatus Competency and Commitment on the Performance of Regional Work Units in Bandung District - M.Yusuf Sanny; Cucu Endang; Tedy Hidayat; Andreas Wahyu Gunawan P; Stefanus M S Sadana (Budapest International Research and Critics University, 2022)
Human resources in the state apparatus are an important aspect of the running of government activities both at the regional and central levels. Problems in human resources certainly have an impact on government performance, so it is necessary to research to understand aspects of the dimensions of human resources on organizational performance. The object of this research is the Regional Work Unit (SKPD) in Bandung Regency, the research approach uses quantitative with the research method to be carried out is analytical descriptive. The target population in this study were all SKPDs of Bandung Regency, using purposive sampling. The technical analysis of the data in this study uses an analysis design and hypothesis testing in the form of validity testing, reliability testing, path analysis, and partial or simultaneous hypothesis testing. The results showed that simultaneously apparatus competence and apparatus commitment had a positive effect on SKPD performance in Bandung Regency, partially apparatus competence had a positive effect on SKPD performance in Bandung Regency and partially apparatus commitment had a positive effect on SKPD performance in Bandung Regency.